Intestinal microsporidiosis: a new entity in Malaysia? - Awang Hamat, Rukman; Osman, Malina; M. I., Noorhayati; Mohammad, Marlyn; Abdullah, Wan Omar; Abd. Majid, Roslaini; Unyah, Ngah Zasmy; Moktar, Norhayati (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2008)
Objective: Intestinal microsporidia is an emerging human disease caused by microsporidia. A study was conducted to determine the prevalence of microsporidia in patients with gastro-intestinal symptoms and to examine the clinical manifestations associated with intestinal microsporidiosis. Methods: A descriptive cross-sectional study using a well-structured questionnaire; a review of medical records was also undertaken. Positive stool samples were defined as presence of one or more pinkish-violet ovoid structures with a belt-like stripe under high power field (100x) using modified gram-chromotrope stain (MGC). Results: A total of 353 faecal specimens of patients was examined and 100 patients were found to have positive stool samples for microsporidia. The overall prevalence of microsporidia was 28.3%. Acute and chronic diarrhoea were seen in 49.0% and 36.0% patients, respectively. The commonest clinical presentations were diarrhoea (85.0%) with 83.0 % of patients having loose or watery stools, vomiting (75.0%), foul-smelling stools (60.0%), nausea (59.0%) and cramping abdominal pain (39.0%). The least common symptoms were fever (15.0%), mucous in stool (5.0%) and blood in stool (4.0%). Conclusion: This study concludes that the prevalence of microsporidia is still high (28.3%) and the majority of patients (93.0%) are symptomatic; the most common gastro-intestinal symptom is diarrhoea with loose or watery stools. Hence, it is recommended that a stool screening for microsporidia be done in selected patients presented with gastrointestinal symptoms.